PROGRAMMING AND ROBOTICS BASED IN STEAM LEARNING - Gulshod Yunusova Nazikhovna (Journals Park Publishing, 2022)
This article shows which areas of Steam education need to be developed to train small and highly qualified specialists. The author shows the future development of production, mechanical engineering and robotics, engineering and invention, now and in the future, the creation and application of Smart technologies, the construction of Smart houses and apartments, Smart cities is based on the level of knowledge and preparedness of small and highly qualified specialists who need to be trained on additional education courses, because there is barely enough time in an educational institution to cover the material on the curriculum and the standard of education.
Keywords: TinkerCad Program; Arduino Program; Python Programming